YouTubeTM as a source of information on bladder pain syndrome: A contemporary analysis. Issue 1 (24th September 2021) - Morra, Simone; Collà Ruvolo, Claudia; Napolitano, Luigi; La Rocca, Roberto; Celentano, Giuseppe; Califano, Gianluigi; Creta, Massimiliano; Capece, Marco; Turco, Carmine; Cilio, Simone; Melchionna, Alberto; Gerundo, Gerardo; et al.
Abstract: Aim: To evaluate the quality of YouTube™ videos on bladder pain syndrome (BPS) and to investigate whether they can be used as a reliable source of information. Methods: The search term "bladder pain syndrome" was used on YouTube TM platform. The first 100 videos were selected. Patient Education Materials Assessment Tool for audio‐visual content (PEMAT A/V), Global Quality Score (GQS), Misinformation tool, and DISCERN score were used to assess videos' quality content. Pearson's test was used to assess potential correlations between variables. Results: Seventy‐nine videos were suitable for the analyses. The median PEMAT A/V Understandability score and PEMAT A/V Actionability score were 66.7% (interquartile range [IQR]: 46.2–100.0) and 75.0% (IQR: 37.5–100.0), respectively. According to GQS, 26 (32.9%), 32 (40.5%), 3 (3.8%), 15 (19.0%), and 3 (3.8%) videos were excellent, good, moderate, generally poor, and poor, respectively. According to Misinformation tool, of all videos, 81% ( n = 64), 6.3% ( n = 5), 5.1% ( n = 4), 5.1% ( n = 4), 2.5% ( n = 2) had respectively no, very little, moderate, high, and extreme misinformation. The overall median DISCERN score ranged from 5.0 (IQR: 2.0–5.0) to 5.0 (IQR: 5.0–5.0). A positive statistically significant correlation was found between video length and PEMAT A/V Understandability ( r = 0.27, p = 0.01), video length and PEMAT A/V Actionability ( r = .26, p = 0.02), and video length and DISCERN Question 16 ( r = 0.28, p = 0.01). Conclusions: Nowaday, the overall quality of YouTube TM videos on BPS have been evaluated good according to PEMAT A/V, GQS, Misinformation tool, and DISCERN score. It is possible to assume that YouTube TM may be considered as a reliable source of information on BPS.